Teachers' Work Stress in the Implementation of the Independent Curriculum: an Analysis of the Role of Self-Efficacy - Airin, Evelyn; Hartini, Sri; Collin, Justine; Theransq, Kathaleeya; Indayani, Endang; Putrie Dimala, Cempaka (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Work stress was one of the factors that could affect the effectiveness of educators in carrying out their duties. Self-efficacy, as an individual's belief in their own abilities, was often considered to reduce the negative impact of work stress. However, the results of this study indicated that the relationship between self-efficacy and work stress was complex and not always protective. This study aimed to analyze the relationship between self-efficacy and work stress among educators at Global Prima. The method used in this study was a quantitative approach with partial correlation techniques to determine the relationship between variables after controlling for other influencing factors. The research instrument used a Likert scale consisting of a work stress scale and a self-efficacy scale. The results showed a positive relationship between self-efficacy and work stress. These findings indicated that educators with high self-efficacy levels actually experienced higher levels of work stress. Partial correlation analysis showed that aspects of work stress and self-efficacy had varying relationships. The implications of this study suggested that increasing self-efficacy should be accompanied by effective stress management strategies to avoid increasing the psychological burden on educators. Stres kerja merupakan salah satu faktor yang dapat memengaruhi efektivitas tenaga pendidik dalam menjalankan tugasnya. Self-efficacy sebagai keyakinan individu terhadap kemampuannya sendiri sering dianggap dapat mengurangi dampak negatif dari stres kerja. Namun, hasil penelitian ini menunjukkan bahwa hubungan antara self-efficacy dan stres kerja bersifat kompleks dan tidak selalu bersifat protektif. Penelitian ini bertujuan untuk menganalisis hubungan antara self-efficacy dan stres kerja pada tenaga pendidik di Global Prima. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan teknik korelasi parsial untuk mengetahui hubungan antar variabel setelah mengontrol faktor lain yang berpengaruh. Instrumen penelitian menggunakan skala Likert yang terdiri dari skala stres kerja dan skala self-efficacy. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara self-efficacy dan stres kerja. Temuan ini mengindikasikan bahwa tenaga pendidik dengan tingkat self-efficacy yang tinggi justru mengalami tingkat stres kerja yang lebih tinggi. Analisis korelasi parsial menunjukkan bahwa aspek stres kerja dan self-efficacy memiliki hubungan yang bervariasi. Implikasi dari penelitian ini menunjukkan bahwa peningkatan self-efficacy harus disertai dengan strategi manajemen stres yang efektif agar tidak meningkatkan beban psikologis tenaga pendidik.